Epidemiological profile of patients with malaria admitted to the Erasmo Meoz University Hospital in the municipality of Cúcuta, during the period 2014-2021: Perfil epidemiológico de pacientes con malaria que ingresan al Hospital Universitario Erasmo Meoz del municipio de Cúcuta, durante el periodo 2014-2021 (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
The objective of this research is to describe the epidemiological profile of patients with malaria who enter the ESE HUEM of the Municipality of San José de Cúcuta, during the period 2014-2021. A cross-sectional observational epidemiological study is developed, which seeks to determine the prevalence of patients with malaria admitted to this hospital during the study period; Variables associated with sex, age, clinical manifestations, type of parasite, etc. are taken into account. The analysis of the results allows us to determine that the highest percentage of patients treated are of Colombian nationality (67.74%), although there is a high presence of Venezuelan patients (32.26%). Fever is presented as the clinical manifestation with the highest diagnosis in patients admitted to the hospital for this pathology (91.36%). The Plasmoidum vivax species is recorded as the parasite with the greatest presence. The male sex has a higher prevalence of hospitalization. When analyzing the age range with the highest risk of malaria infection, patients between 15 and 59 years old are recorded as the population that is hospitalized most frequently.